New HPMA copolymer-based drug carriers with covalently bound hydrophobic substituents for solid tumour targeting - Chytil, P; Etrych, T; Konák, C; Sírová, M; Mrkvan, T; Boucek, J; Ríhová, B; Ulbrich, K (Journal of controlled release, 2008)
Various conjugates of anticancer drug doxorubicin (Dox) covalently bound by the hydrolytically degradable hydrazone bond to the drug carrier based on N-(2-hydroxypropyl)methacrylamide (HPMA) copolymers were synthesised. Structure of the conjugates differed in the type and the content of hydrophobic substituent (dodecyl, oleic acid and cholesterol moieties) introduced into the polymer structure. In aqueous solutions the conjugates self-assembled into high-molecular-weight supramolecular structures, such as polymeric micelles or stable hydrophilic nanoparticles 13-37 nm in diameter, depending on the type and the content of hydrophobic substituents. Treatment of mice bearing EL-4 T cell lymphoma with the conjugates in the therapeutic regime of drug administration (i.v.) resulted in significant tumour regression with up to 100% of long-term survivors, depending on the dose and the detailed structure of the carrier. The nanoparticles formed by the conjugate bearing cholesterol moiety exhibited prolonged blood circulation and enhanced tumour accumulation indicating an important role of the EPR effect in excellent anticancer activity of the conjugate.
Keywords: kyseliny polymethakrylové; Animals; Doxorubicin; Methacrylates; proliferace buněk; Hydrophobic and Hydrophilic Interactions; Cell Line, Tumor; methakryláty; protinádorová antibiotika; Neoplasms; nádory; Drug Carriers; lidé; Mice; transplantace nádorů; Antibiotics, Antineoplastic; myši; Polymethacrylic Acids; hydrofobní a hydrofilní interakce; doxorubicin; Cell Proliferation; nosiče léků; Neoplasm Transplantation; zvířata; Mice, Inbred C57BL; nádorové buněčné linie; myši inbrední C57BL; Humans